ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2019
DOI: 10.1109/icassp.2019.8682995
|View full text |Cite
|
Sign up to set email alerts
|

Objective Assessment of Vocal Tremor

Abstract: Detecting early signs of neurodegeneration is vital for planning treatments for neurological diseases. Speech plays an important role in this context because it has been shown to be a promising early indicator of neurological decline, and because it can be acquired remotely without the need for specialized hardware. Typically, symptoms are characterized by clinicians using subjective and discrete scales. The poor resolution and subjectivity of these scales can make the earliest speech changes hard to detect. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…The following data collection tools and methods were used in this study: 7 These results will be reported separately. 5 Activity tracker.…”
Section: Measurement Tools and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following data collection tools and methods were used in this study: 7 These results will be reported separately. 5 Activity tracker.…”
Section: Measurement Tools and Methodsmentioning
confidence: 99%
“… Speech analysis . A separate ALS AT HOME speech app and database was developed by Aural Analytics (Phoenix, Arizona, USA) 7 . These results will be reported separately. Activity tracker .…”
Section: Methodsmentioning
confidence: 99%
“…Tremor features displayed the strongest effect size when comparing preHD and Controls. But the unequal level of data loss in each group (51% HD, 38% preHD, and 25% Controls) suggests defining estimation methods that incorporate tremor instability and better tremor tracking methods [14] for future work.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have used sustained phonation for the assessment of various neurodegenerative disorders such as Parkinson's disease [13], Amyotrophic Lateral Sclerosis [14] and also Huntington's Disease [10]. These studies have extracted a number of hand-crafted features from the sustained phonation and built discriminative models to distinguish patients from controls.…”
Section: Related Workmentioning
confidence: 99%
“…We show that this representation correlates strongly with clinical perception of hypernasality across several different neurological disorders, even when trained on one disorder and evaluated on a different disorder. Such assessment has a potential advantage as an inexpensive, non-invasive and simple-to-administer method, scalable to large and diverse populations [57] [58].…”
Section: B Contributionsmentioning
confidence: 99%